2001
DOI: 10.1074/jbc.m008628200
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of a Mobile Loop in Regulating Chaperonin/ Co-chaperonin Interaction

Abstract: Chaperonins are universally conserved proteins that nonspecifically facilitate the folding of a wide spectrum of proteins. While bacterial GroEL is functionally promiscuous with various co-chaperonin partners, its human homologue, Hsp60 functions specifically with its co-chaperonin partner, Hsp10, and not with other cochaperonins, such as the bacterial GroES or bacteriophage T4-encoded Gp31. Co-chaperonin interaction with chaperonin is mediated by the co-chaperonin mobile loop that folds into a ␤-hairpin confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 58 publications
4
66
0
2
Order By: Relevance
“…Presence of the respective variations and absence of mutagenesisinduced PCR errors was established by sequencing and subcloning. The resulting vectors were used in the genetic complementation assay described previously (Hansen et al 2002;Richardson et al 2001).…”
Section: Analysis Of Missense Variationsmentioning
confidence: 99%
“…Presence of the respective variations and absence of mutagenesisinduced PCR errors was established by sequencing and subcloning. The resulting vectors were used in the genetic complementation assay described previously (Hansen et al 2002;Richardson et al 2001).…”
Section: Analysis Of Missense Variationsmentioning
confidence: 99%
“…The mitochondrial Hsp60 (mHsp60) 3 is similar to GroEL in that it is made up of heptameric rings (12-14) that can refold denatured substrates in vitro with the assistance of a co-chaperonin and ATP (15). However, the mHsp60 oligomer is less stable than the bacterial homolog, and it exhibits unique nucleotide binding properties and specificity for co-chaperonin (13,14,16).In addition to their essential function in mediating protein folding, the mammalian mitochondrial chaperonins were also suggested to be involved in extramitochondrial activities. A number of reports have suggested that mHsp60 can stimulate human leukocytes and vascular endothelial cells to produce proinflammatory cytokines (17).…”
mentioning
confidence: 99%
“…The mitochondrial Hsp60 (mHsp60) 3 is similar to GroEL in that it is made up of heptameric rings (12)(13)(14) that can refold denatured substrates in vitro with the assistance of a co-chaperonin and ATP (15). However, the mHsp60 oligomer is less stable than the bacterial homolog, and it exhibits unique nucleotide binding properties and specificity for co-chaperonin (13,14,16).…”
mentioning
confidence: 99%
“…Therefore, the folding of at least 16 residues is coupled to the binding of 3 residues to GroEL. A multitude of mutations in the mobile loops of GroES and other co-chaperonins is known to affect function (11,(13)(14)(15)(16)(17)(18)(19)(20). Since many of these mutations occur away from residues directly involved in forming the binding interface, we have hypothesized that the mutations affect the folding transition (16).…”
mentioning
confidence: 99%
“…Since many of these mutations occur away from residues directly involved in forming the binding interface, we have hypothesized that the mutations affect the folding transition (16). For example, amino acid substitutions within the mobile loop of GroES but outside of the GroELbinding tripeptide were shown to increase the affinity of GroES for both GroEL and Hsp60, the human mitochondrial homologue (19). The increase in affinity was explained as being a result of decreasing the disorder of the mobile loop or, conversely, preordering the binding structure of the mobile loop.…”
mentioning
confidence: 99%